Passband Characteristic of MM Fibers - Siuzdak, Jerzy; Kowalczyk, Maciej; Maksymiuk, Lech; Stepniak, Grzegorz (Photonics Letters of Poland, 2009)
Frequency response of Multimode (MM) fibers beyond the baseband is studied. It is shown that in the absence of mode group mixing there are relative flat passbands suitable for transmission in such fibers if the number of mode groups propagating is not too large. Such conditions are usually met for typical contemporary graded index (GI) silica fibers. It is also proved that the passbands width is related to the baseband width. Moreover, the 1300 nm window is the most suitable for transmission due to small chromatic dispersion and reduced number of mode groups propagating.